1997
DOI: 10.3354/dao030099
|View full text |Cite
|
Sign up to set email alerts
|

Fish-to-fish transmission of a marine myxosporean

Abstract: ABSTRACT. F~sh-to-fish transmission of the marine myxosporean Myxidium lee; was experinlentally demonstrated in sea bream Sparus aurata L. A group of specif~c-pathogen-free (SPF) fish of -11 g each were placed in a wire-mesh cage immersed In a tank holding infected fish. A second group was placed in a tank receiving water discharged from another tank holding diseased fish. After 9 wk, the fish were sacrificed and 12 of the 38 (31.6%) test fish from the mesh cage were found to harbor trophozoites, sporoblasts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 10 publications
8
89
0
1
Order By: Relevance
“…K. clupeidae may even be associated with host mortality (Lom & Dyková 1992). Modes of transmission may vary between species as both direct (Diamant 1997) and indirect (Koie et al 2004) life cycles have been reported for marine myxozoans. Thus, although these species have very similar SSU rDNA sequences and are morphologically similar, their epidemiological relevance to fisheries differs.…”
Section: Resultsmentioning
confidence: 99%
“…K. clupeidae may even be associated with host mortality (Lom & Dyková 1992). Modes of transmission may vary between species as both direct (Diamant 1997) and indirect (Koie et al 2004) life cycles have been reported for marine myxozoans. Thus, although these species have very similar SSU rDNA sequences and are morphologically similar, their epidemiological relevance to fisheries differs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, fish-to-fish transmission of Myxidium leei was experimentally demonstrated in the sea bream Sparus auratus by Diamant (1997), who suggested such direct transmission may be a model for the development of other marine myxosporeans. The estuarine origins of K. clupeidae may offer some insight into the diversity of life cycles with varying salinity.…”
Section: Kudoa Clupeidae Development In Atlantic Menhadenmentioning
confidence: 99%
“…Ulcers have been observed in Atlantic menhaden Brevoortia tyrannus (Clupeidae) along the east coast of the USA, primarily from North Carolina to Maryland, for many years (Dykstra et al 1989, Levine et al 1990a,b, Kane et al 1998. Cultures of ulcers from wild fishes have yielded fungi , Levine et al 1990b, Blazer et al 1999) and various bacteria (Te Strake & Lim 1987, Dykstra et al 1989, Baya et al 1990, 1997. Recently, some investigators have proposed a causal relationship between harmful algal bloom fish mortalities, such as those caused by Pfiesteria piscicida, and the presence of ulcers on Atlantic menhaden (Noga et al 1996, Burkholder & Glasgow 1997, Noga 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Enteromyxum leei is a myxosporean enteric parasite seriously affecting Mediterranean sparid cultures (Palenzuela, 2006;Sitjà-Bobadilla and Palenzuela, 2011). The parasite has been experimentally transmitted by cohabitation with infected fish, oral intubation with infected intestinal scrapings, exposure to water from infected tanks (effluent transmission) and by anal intubation (Diamant, 1997;Diamant and Wajsbrot, 1997;Sitjà-Bobadilla et al, 2007;Estensoro et al, 2010). It was first described in cultured gilthead sea bream (Diamant, 1992) but it has since been detected in many ornamental and cultured fish in the Canary Islands, the Mediterranean and Red Sea and in Western Japan .…”
Section: Introductionmentioning
confidence: 99%